Visualization of Microseismic Processing by Coding with GNU Octave - Purnama, Aditya Yoga; Nurhanafi, Kholis; Susanti, Susanti; Wibowo, Nugroho Budi (Navigation Physics : Journal of Physics Education, 2025)
The use of software in the field of geophysics is often limited to the instantaneous use of interfaces without a deep understanding of the computational processes behind them. This leads to limitations in data interpretation and the development of new methods. To address this issue, it is necessary to explicitly visualize the data processing process through programming in order to strengthen computational thinking skills, which are one of the important competencies of the 21st century. This study aims to visualize the microseismic data processing process using programming in GNU Octave software. The method used is a simulation of microseismic data processing based on the HVSR (Horizontal to Vertical Spectral Ratio) approach, with field data collected from the Yogyakarta area. The processing is carried out by building a programming script in GNU Octave, the results of which are then compared with the Geopsy software as a verification tool. The research results indicate that data processing visualization using the HVSR method through GNU Octave can be performed effectively, and the results exhibit high consistency with the output from Geopsy. The dominant frequency on both curves is the same at a frequency of 1.59 Hz. In addition to the dominant frequency, the HVSR curve shape of both software also shows a similar trend pattern in the mid to high frequency range (around 2–10 Hz), where the amplification value decreases gradually. This demonstrates the accuracy of the developed script and proves that this approach can serve as an educational tool for understanding the functioning of geophysical software in a more transparent and in-depth manner. Programming with GNU Octave can be used as an efficient and accurate geophysical analysis tool. This provides opportunities for users, especially in academic environments with limited access to commercial software.